Uniqueness And Unfavorable of Clinical and Medical Diagnosis of Pulmonary Tuberculosis - Jumaev Mukhtor Fatullaevich (Academia One Publishing, 2023)
The low level of effectiveness in the treatment of tuberculosis patients is due to the lack of timely diagnosis and control of chemotherapy, as well as effective modern drugs. In the material of the analysis of 152 medical records of patients with pulmonary tuberculosis, performed in accordance with the standards, it was found that out of 37 diagnostic criteria, the majority are either rarely used or not used at all. Along with this, it should be noted that some of them are of a general nature and do not always affect the quality of diagnosis. It was decided to consider a minimum set of diagnostic criteria sufficient, but when conducting an appropriate medical examination, it is necessary to request, through the investigator, an explanation from the attending physician responsible for establishing the diagnosis of pulmonary tuberculosis.
Keywords: pulmonary tuberculosis; diagnosis; quality of medical care